161k views
1 vote
Consider the polynomial function P(x)=2x³+3x²-2x-3.Verify that P(−1) = 0. Since P(−1) = 0, what must one of the factors of P be?

User Squeaky
by
5.0k points

2 Answers

4 votes

Final answer:

To verify that P(-1) = 0, substitute -1 into the polynomial function P(x) = 2x³ + 3x² - 2x - 3. The factor of P(x) is (x + 1).

Step-by-step explanation:

To verify that P(-1) = 0, we substitute -1 into the polynomial function P(x) = 2x³ + 3x² - 2x - 3.

P(-1) = 2(-1)³ + 3(-1)² - 2(-1) - 3

Simplifying this expression, we get P(-1) = -2 + 3 + 2 - 3 = 0.

Since P(-1) = 0, it means that (x + 1) is one of the factors of the polynomial function P(x).

User Renna
by
4.7k points
4 votes

Answer:

So (x+1) will be the one of factor of given polynomial

Step-by-step explanation:

We have given the equation
2x^3+3x^2-2x-3

First we have to find the value of
p(-1)

For finding
p(-1) we have to put x = -1 in the polynomial

So
p(-1)=2* (-1)^3+3(1)^2-2* (-1)-3=-2+3+2-3=0

As
p(-1) is zero so x = -1 will be the root of the given polynomial

So (x+1) will be the one of factor of given polynomial

User Mark Otaris
by
4.5k points